What Next for Human Space Flight?. (November 2014) - Sherwood, Brent
<x xml:space="preserve">Abstract</x> Space travel is undergoing a significant period of transformation. While exploration in the last six decades has been driven by government‐funded exploration by the major powers, the possibilities are now opening up for a Space Architecture that diversifies and caters for leisure, large‐scale industrialization and permanent settlement. Experienced space architect Brent Sherwood brings into focus four potential futures for human space flight ‐ experiencing, exploring, exploiting and settling.